+0  
 
0
507
4
avatar

f(x) = tan^-1(2x+1)

 Dec 6, 2014

Best Answer 

 #4
avatar+20831 
+10

f(x) = tan^-1(2x+1)      f(x)'  ?

$$\tan[\ \textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ ] = 2x+1 \quad | \quad \frac{\ d()}{dx} \quad \small{\text{ and }} \quad \boxed{ [ \ tan(x)\ ]' = 1+\tan^2(x) }\\\\
(1+\tan^2(\ \textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ ) )
\times
\left[\ \textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ \right]'
= 2
\\\\
\left[ 1+(2x+1)^2} \right]
\times
\left[\textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ \right]'
= 2 \\\\
\boxed{ \left[\ \textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ \right]'
= \frac{2} {1+(2x+1)^2} } }$$

.
 Dec 8, 2014
 #1
avatar+27342 
+5

Derivative

.

 Dec 6, 2014
 #2
avatar
+10

Thanks for your answer. I really would love some explanation and if you can show me how to solve this problem by using u-substituiton I would appreciate.

 

Thanks again. :)

 Dec 6, 2014
 #3
avatar+95177 
+10

$$\\y=tan^{-1}(2x+1)\\\\
Let\;\; u=2x+1\qquad \frac{du}{dx}=2\\\\
y=tan^{-1}\;u\\\\
u=tan\;y\\\\
\frac{du}{dy}=sec^2y\\\\
\frac{dy}{du}=\frac{1}{sec^2y}\\\\$$

 

--------

 

$$\\y=tan^{-1}(2x+1)\\\\
Let\;u=2x+1\qquad \frac{du}{dx}=2\\\\
y=tan^{-1}u\\\\
u=tan\;y\\\\
\frac{du}{dy}=sec^2y\\\\
\frac{dy}{du}=\frac{1}{sec^2y}\\\\
\begin{array}{rll}
\frac{dy}{dx}&=&\frac{dy}{du}\times\frac{du}{dx}\\\\
&=&\frac{1}{sec^2y}\times 2\\\\
&=&\frac{2}{sec^2y}\\\\
&=&$refer to explanation below to help get to next step$\\\\
&=&\frac{2}{1+u^2}\\\\
&=&\frac{2}{1+(2x+1)^2}\\\\
&=&\frac{2}{4x^2+4x+2}\\\\
&=&\frac{1}{2x^2+2x+1}\\\\
\end{array}$$

 

--------------------

 tan y = u/1

 Dec 7, 2014
 #4
avatar+20831 
+10
Best Answer

f(x) = tan^-1(2x+1)      f(x)'  ?

$$\tan[\ \textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ ] = 2x+1 \quad | \quad \frac{\ d()}{dx} \quad \small{\text{ and }} \quad \boxed{ [ \ tan(x)\ ]' = 1+\tan^2(x) }\\\\
(1+\tan^2(\ \textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ ) )
\times
\left[\ \textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ \right]'
= 2
\\\\
\left[ 1+(2x+1)^2} \right]
\times
\left[\textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ \right]'
= 2 \\\\
\boxed{ \left[\ \textcolor[rgb]{1,0,0}{\tan^{-1}(2x+1)} \ \right]'
= \frac{2} {1+(2x+1)^2} } }$$

heureka Dec 8, 2014

6 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.